2013
DOI: 10.5812/ijhrba.8409
|View full text |Cite
|
Sign up to set email alerts
|

Ovary Cells Apoptosis in Opium-Addicted Diabetic and Non-Diabetic Rats

Abstract: BackgroundApoptosis is a physiological mechanism of cell death and it can be triggered by a variety of internal and external stimuli. It has been indicated that some opium derivatives develop cell apoptosis.ObjectivesThe aim of this investigation was to evaluate the effect of opium addiction on ovary cell apoptosis in diabetic and non-diabetic Wistar rats.Materials and MethodsThis experimental study was done on control, control-addicted, diabetic and diabetic-addicted rats. DNA fragmentation as a biomarker of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The relationship between hyperglycemia and the induction of apoptosis has already been established, and studies have reported the presence of excess apoptosis in the ovarian cells of diabetic rats [22,83,85] and in the ovaries of rats that consumed an HFD by increasing the expression of Bax and caspase-3 in addition to other apoptotic markers [18,52,86,87]. However, our results are controversial.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The relationship between hyperglycemia and the induction of apoptosis has already been established, and studies have reported the presence of excess apoptosis in the ovarian cells of diabetic rats [22,83,85] and in the ovaries of rats that consumed an HFD by increasing the expression of Bax and caspase-3 in addition to other apoptotic markers [18,52,86,87]. However, our results are controversial.…”
Section: Discussionmentioning
confidence: 60%
“…Apoptosis is a complex process involving intrinsic and extrinsic activation pathways by pro-and anti-apoptotic proteins coordinated by normal mitochondrial function [81]. Studies have demonstrated that the intrinsic pathway of apoptosis controlled by the Bcl-2 family has an important role in oocyte survival and in the maintenance of the ovarian reserve [82]; changes in this pathway, such as the increased activation of pro-apoptotic members (e.g., Bax) and a decrease in anti-apoptotic members (e.g., Bcl-2) compromise reproduction through caspase-3-mediated cell death [22,83]. Furthermore, impaired cell proliferation prevents adequate follicular development and oocyte maturation, leading to reproductive dysfunction [84].…”
Section: Discussionmentioning
confidence: 99%
“…Increased blood sugar in the patients is an important cause of several complications including cardiovascular diseases, neuropathy, retinopathy, kidney failure, amputations and so on (4,7). Obesity, unsuitable diet, not enough exercise, genetics, hormones and environmental factors are the main reasons for insulin resistance but some environmental factors such as stress and mental diseases deteriorate the disease (5,8). Inflammation is a common phenomenon in T2D which is associated with the mentioned complications (1,9).…”
Section: Type 2 Diabetesmentioning
confidence: 99%